DETERMINASI MEDIA DALAM MENGAWAL DAN MENDORONG PENEGAKAN HUKUM MELAWAN KORUPSI - Amir Machmud N.S. (Faculty of Law, Universitas Diponegoro, 2013)
Abstract One of several functions of the press, that is social control, is such an explanation of an insight that the freedom of press is intended to prevent corruption, collution, and nepotism as well. The press applies the function as mentioned in The Law No 40 of 1999 regarding The Press, that is to control the performance of the state adminstration in order to keep it accountable and transparent. In reality, the growing abuse of power in Indonesia have been creating in condition of so called “corruption emergency”. The establishment of Corruption Eradication Comission (KPK) shows us that the regular law institutions are not doing their properly. We need such a comission with extraordinary power. Realizing of power of KPK, many corrupt government officialsand members of parliament definitely feel anxious, so they try hard to make massive and systematic resistance againts the comission. That’s why, the efforts to eradicate corruption need support and involvement from civil society. Journalist and media are determinate factor to endorse those efforts by using its social control function. Media determinate the law enforcement againts corruption by providing reports and news stories based on framing policy, by constructing reality for public interests. Keywords : Social control, Freedom of press, Corruption eradication, Framing policy, Editorial policy. Abstrak Salah satu fungsi pers, yakni melaksanakan kontrol sosial, merupakan penjabaran dari pemahaman bahwa kemerdekaan pers mencegah korupsi, kolusi, dan nepotisme. Pers memainkan fungsi tersebut sebagai amanat dari Undang-Undang Nommor 40 Tahun 1999 tentang Pers untuk mengawal penyelenggaraan negara dan pemerintahan yang akuntabel dan transparan. Dalam realitas penyelenggaraan negara itu, penyalahgunaan kekuasaan merupakan keniscayaan yang di Indonesia sekarang ini menciptakan kondisi “darurat korupsi”. Keberadaan Komisi Pemberantasan Korupsi (KPK) menggambarkan bahwa lembaga-lembaga hukum reguler tidak berjalan secara maksimal, sehingga membutuhkan sebuah komisi dengan kewenangan yang luar biasa. Namun karena keterancaman orang-orang yang berada di pusat-pusat kekuasaan, perlawanan-perlawanan terhadap komisi antirasuah itu berlangsung secara masif dan sistematis, sehingga untuk mewujudkan amanat rakyat dalam memberantas korupsi dibutuhkan pengawalan dari elemen-elemen masyarakat sipil. Wartawan dan media menjadi faktor determinan dalam menjalankan pengawalan itu melalui fungsi kontrol sosialnya. Media mendeterminasi penegakan hukum melawan korupsi dengan mengetengahkan kebijakan pemberitaan yang berbasis framing atau pembingkaian dengan mengonstruksi realitas yang berorientasi pada sebesar-besarnya kemaslahatan publik. Kata Kunci : Kontrol sosial, Kemerdekaan pers, Pemberantasan korupsi, Framing, kebijakan pemberitaan.